(untitled) (Global Journal of Human-Social Science, 2018)
The study examined the influence of gender stereotyping on achievement in Basic Science among Upper Basic Education School UBES students in Toto LGA Nasarawa State Nigeria The study was a descriptive survey design The population of the study consisted of all the public upper basic III students The study employed a sample size of 300 students drawn from the population using simple random sampling A researcher designed questionnaire titled Gender Based Questionnaire on Students Achievement in Basic Science GBQSABS was used for data collection Data was analysed employing descriptive statistics to answer the research question while Chi Square statistics was used to test the research hypothesis at alpha 0 05 The finding of the study show that gender stereotyping has no significant influence on students achievement in Basic Science